Multilocus Sequence Typing Reveals Relevant Genetic Variation and Different Evolutionary Dynamics among Strains of Xanthomonas arboricola pv. juglandis - Marco Scortichini; Patrizia Ferrante; Simone Marcelletti (Diversity, 2010)
Forty-five Xanthomonas arboricola pv. juglandis (Xaj) strains originating from Juglans regia cultivation in different countries were molecularly typed by means of MultiLocus Sequence Typing (MLST), using acnB, gapA, gyrB and rpoD gene fragments. A total of 2.5 kilobases was used to infer the phylogenetic relationship among the strains and possible recombination events. Haplotype diversity, linkage disequilibrium analysis, selection tests, gene flow estimates and codon adaptation index were also assessed. The dendrograms built by maximum likelihood with concatenated nucleotide and amino acid sequences revealed two major and two minor phylotypes. The same haplotype was found in strains originating from different continents, and different haplotypes were found in strains isolated in the same year from the same location. A recombination breakpoint was detected within the rpoD gene fragment. At the pathovar level, the Xaj populations studied here are clonal and under neutral selection. However, four Xaj strains isolated from walnut fruits with apical necrosis are under diversifying selection, suggesting a possible new adaptation. Gene flow estimates do not support the hypothesis of geographic isolation of the strains, even though the genetic diversity between the strains increases as the geographic distance between them increases. A triplet deletion, causing the absence of valine, was found in the rpoD fragment of all 45 Xaj strains when compared with X. axonopodis pv. citri strain 306. The codon adaptation index was high in all four genes studied, indicating a relevant metabolic activity.